Improving the use of remote laboratories. The case of VISIR at Universidad Nacional de Rosario - Lerro, Federico (2021)
The present work originates in the Project "Educational Modules for Electric and Electronic Circuits Theory and Practice following an Inquiry-based Teaching and Learning Methodology supported by VISIR", carried out with the support of the Erasmus+ Programme. Remote labs can provide a framework where physical experiments can be developed for STEM (Science, Technology, Engineering and Mathematics) education. Although remote labs have been in use for over a decade now in several countries and levels of education, their use is not yet being generalized in Latin America. Through the VISIR+ International Cooperation Project from the Erasmus+ Programme, five higher education institutions from Latin America have incorporated de VISIR remote lab in order to carry out experiments with electric and electronic circuits. In the present work, the results of the study developed at Universidad Nacional de Rosario within the framework of the aforementioned project are shown.